The Impact of Prices of Tourism Hosting Products and Services on Hotel Sector Inflation - Salgado Zenha Carneiro, Paulo (2022)
The hotel sector, as well as the tourism sector, have great impacts on the world economy, were one of the main hits in the pandemic period, this fact raised the question of what would happen to the prices of these services, so this survey seeks to identify which the impact on the prices of tourist accommodation facilities in the face of the pandemic caused by COVID - 19, for that, an exploratory and descriptive investigation with a quantitative and qualitative approach was necessary. As a main result, it was found that there was a variation in prices during this period that humanity passed, however, the proposal is not to exhaust the theme since the economic and social effects have not yet been fully quantified.